The Effect Of School Locations, Facilities And Images On Decisions To Choose Office Competency Office Of Administration In Bonavita Vocational School - Winarsih, Winarsih; Surip, Ngadino (International Journal for Educational and Vocational Studies, 2020)
This study aims to determine the relationship between location variables, facilities and school image of the decision to choose office administration competency competencies. To determine the relationship between location variables, facilities and school image, this study used a saturated sample technique of 81 respondents consisting of class X, XI, and XII Bonavita Vocational School. This study uses a quantitative analysis method with multiple linear regression analysis tools with SPSS version 23. From the analysis of test results obtained, simultaneously (F-Test ) the location, facilities and school image significantly influence the decision to choose the competency of office administration expertise at Bonavita Vocational School . Partial analysis testing (T-test) location, facilities and school image significantly influence the decision to choose office administration competency competency at Bonavita Vocational School. While the results of correlation analysis and determination obtained Adjusted R Square 0.732 results mean the location, facilities and school image determine the decision to choose a school by 73.2% while the remaining 26.8% are determined by other variables not examined in this study. And the correlation between variables is included in the strong relationship category.